(Dis)Ableing Notions of Authentic Leadership Through the Lens of Critical Disability Theory. (November 2017) - Procknow, Greg; Rocco, Tonette S.; Munn, Sunny L.
The Problem: Persons with disabilities (PWD) are regarded as "the Other" and are sequestered from "normative" society because of their "Otherness." "Othering" results in discrimination and the systemic preclusion of PWD. Ableism is the belief that being without a disability, impairment, or chronic illness is the norm. The notion that people without disabilities are the norm and are inherently superior is accepted without critique by those that advocate for authentic leadership. This privileges ableism and furthers the "Othering" of PWD within a leadership style intended to promote self-awareness, beliefs and ethics, and interpersonal relationships. The Solution: The disabled experience and differently abled voice must be restored through relationally "being" with others and authentic dialogue. What is needed is a shift from the deficit model of authentic leadership to a social paradigm of authentic leadership, welcoming of bodily and psychic difference. This will better enable both leaders and employees to craft an authentic profile in the workplace. The Stakeholders: Leaders and those who seek to become leaders following an authentic leadership approach can benefit from a better understanding of how their ingrained belief systems impact those that they lead who are both "able-bodied" and "disabled." Human resource development (HRD) practitioners and leadership development practitioners can use this information to deconstruct and reconstruct leadership development opportunities to be inclusive as an authentic leader.